The Existence of Single Candidates in the 2024 Regional Elections in Maros Regency - Nasiruddin, Nurfadilah; Nuraliah, Dewi; Fitriani Sari Handayani Razak; Dwi Rianisa Mausili (Journal of Social and Policy Issues, 2025)
The purpose of this study is to analyze the existence of a Single Candidate in the 2024 Regional Head Election in Maros Regency. This study uses a qualitative method with a deductive approach. The research technique is the observation method, namely conducting reflexivity and triangulation and conducting interviews with several agencies such as the Election Supervisory Agency, academics, youth leaders, community organizations and the general public. As well as other sources, namely documents from existing regulations, internet documents and trusted journals. The research was conducted in August - October 2024. The results of the study show that the regional elections will be followed by a Single candidate who is the incumbent, namely the Regent candidate. Initially paired with his partner in the previous period, but because he did not meet the requirements (TMS), there must be a process of replacing the partner in the registration stage. The existence of a Single candidate in the regional elections is also influenced by several things, namely, first, the strength of the Maros Regent candidate who is the incumbent and has social capital and symbolic capital and the strength of support from political parties which is fully held by the Single candidate pair, namely Chaidir Syam-Muetazim. So the pair must advance in the regional head elections against an empty box.